Pengaruh Implementasi Sistem Pengendalian Mutu Internal dan Budaya MutuTerhadap Peningkatan Mutu Pendidikan Tinggi - Tuti Hermelinda; Meriana Meriana; Berlian Afriansyah (Universitas Prof.Hazairin,SH Bengkulu, 2020)
This study used a survey method to examine the effect of the implementation of the Internal Quality Control System and Quality Culture on the Improvement of the Quality of Higher Education in Bengkulu Province. The research method used was a statistical test, namely the effect test with stages; Data Norality Test, Multiple Regression Analysis and Hypothesis Testing. The regression model equation in this study is Y = 14.883 + 0.544X1 + 0.165X2. This equation shows that the increase in each variable X_1 and X_2 will increase variable Y, assuming the other variables are fixed. This means that the implementation of the Internal Quality Control System and Quality Culture will improve the Quality Improvement of Higher Education. Based on the results of the F test, it was obtained a significance value of 0.000 and less than ? = 0.05. This shows that at the 95% confidence level the regression model in this study is declared significant and feasible. The result of multiple linear regression test shows that the value of R2 = 0.371. This shows that the influence of each independent variable, namely the Internal Quality Control System and Quality Culture on the dependent variable, namely the Improvement of the Quality of Higher Education is 36.7%, while the rest is influenced by other factors beyond the one examined by the author. The results of the t-test analysis show that the Internal Quality Control System variable t value is 11.913 with a significance of 0.000. This means that the Internal Quality Control System variable has a significant effect on improving the quality of higher education. Furthermore, the Quality Culture variable shows a positive t value of 3.618 with a significance value of 0.000. This shows that the significance value is less than 0.05 and t is positive so that there is a significant influence between Quality Culture on Improving the Quality of Higher Education.